MicroRNA in Sjögren's Syndrome: Their Potential Roles in Pathogenesis and Diagnosis. (7th June 2018) - Reale, M.; D'Angelo, C.; Costantini, E.; Laus, M.; Moretti, A.; Croce, A.
Abstract : Sjögren's syndrome (SS) or sicca syndrome was described by Swedish ophthalmologist Sjögren in the year 1933 for the first time. The etiology of the SS is multifunctional and includes a combination of genetic predisposition and environmental as well as epigenetic factors. It is an autoimmune disease characterized by features of systemic autoimmunity, dysfunction, and inflammation in the exocrine glands (mainly salivary and lacrimal glands) and lymphocytic infiltration of exocrine glands. In fact, the involvement of lacrimal and salivary glands results in the typical features of dry eye and salivary dysfunction (xerostomia). Only in one-third of the patients also present systemic extraglandular manifestations. T cells were originally considered to play the initiating role in the autoimmune process, while B cells were restricted to autoantibody production. In recent years, it is understood that the roles of B cells are multiple. Moreover, autoantibodies and blood B cell analysis are major contributors to a clinical diagnosis of Sjögren's syndrome. Recently, there has been rising interest in microRNA implication in autoimmunity. Unfortunately, to date, there are only a few studies that have investigated their participation in SS etiopathogenesis. The purpose of this work is to gather the data present in the literature to clarify this complex topic.